THE CONTRADICTORY OF AUSTRALIA PACIFIC SOLUTION TOWARD THE 1951 UNHCR CONVENTION AND 1967 PROTOCOL RELATING TO THE STATUS OF REFUGEE (2001 - 2007) - Yuritia Anggraini Puteri (2011)

(untitled)
Immigration is one of the crucial issues for Australia as a migrant country. There are several reasons why Australia is regarded as the migrant destination country. Not only for economic motive, the immigrant claims themselves as refugee and asylum seekers also make Australia as their destination migrant country. Moreover, the ratification of UNHCR 1951 convention and 1967 Protocol relating to the Status of Refugee make Australia has an international obligation to help UNHCR in solving refugee